PERCEPTIONS AND FACTORS INFLUENCING RICE FARMING ADAPTATION DECISIONS TO CLIMATE CHANGE THREATS IN TRAWAS VILLAGE, MOJOKERTO DISTRICT, EAST JAVA - Hasibuan, Amir Fauzan Martua; Sujarwo, Sujarwo; Syafrial, Syafrial (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Climate change is the phenomenon of changes in global temperature, seasonality and erratic rainfall that have an impact on human activities, changing people's lives, etc. The climate may threaten rice farming income. This research was conducted in Trawas village, Mojokerto district using survey method and purposive sampling using certain criteria. The data obtained were analyzed descriptively regarding perceptions and logistic regression to determine the factors that influence climate change adaptation practices undertaken by farmers. The results of the study based on farmers' perceptions show that 67% of rice farmers feel climate change such as changes in the rainy season (2.76), dry season and rainy season (2.64), air temperature (2.63), the length of the rainy season (2.69), pest and disease attacks (2.79), while the length of the dry season has changed slightly (2.46) with the biggest impact is the increase in pest and disease attacks in the longer rainy season. Socioeconomic factors that positively significantly influence climate change adaptation decisions are education, land status, counseling, and weather information, while the negative and significant effect is the number of family members. These findings imply that farmers, community organizations, and the government must be aware of climate change to reduce the impact of losses on the rice farming sector. Farmers will greatly benefit from the process of farmer adaptation, group involvement, and climate policies from the government such as the provision of drought and flood resistant cultivars, early warning systems, facilities and infrastructure such as improved extension, subsidized superior varieties, fertilizers, and pompanization.